Pengaruh Experiental Marketing Terhadap Minat Berkunjung Kembali Desa Wisata Sindangkasih Garut - Kurniasih, Dewi Rizky Nurafni Amelia; Angguilera, Friskha; Alfattan, Syzco Primason; Azzahra, Nazwa Zaskia; Rahmawati, Prilla; Puspita, Nungky (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study investigates the influence of experiential marketing on tourists’ revisit intention to Sindangkasih Tourism Village in Garut, Indonesia. Recent tourism trends indicate a shift from merely visiting destinations to seeking personalized and emotionally engaging experiences. However, the marketing strategy in many rural tourism areas, including Sindangkasih, still lacks a structured experiential approach. This research aims to examine how five dimensions of experiential marketing sense, feel, think, act, and relate affect tourists' desire to return. A quantitative method was employed using a survey distributed to 96 respondents, selected through purposive sampling. The data were analyzed using multiple linear regression to determine the simultaneous and partial effects of the independent variables. The results reveal that all five dimensions significantly and positively influence revisit intention, both individually and collectively. The coefficient of determination (R²) is 0.655, indicating that 65.5% of the variance in revisit intention is explained by the experiential marketing components, while the remaining 34.5% is attributed to other factors not examined in this study. These findings highlight the crucial role of delivering holistic and memorable tourism experiences in enhancing visitor loyalty in rural destinations. The study suggests that local tourism managers should implement integrated experiential marketing strategies to strengthen emotional bonds with visitors and encourage repeat visits.